Mother Company’s Responsibility for Multinational Subsidiary Activities - Foadi, Hamidreza (Cuestiones Políticas, 2020)
The objective of the article is to analyze the various forms of responsibility of parent companies and their subsidiary multinationals in terms of what corporate social responsibility means. At the methodological level it is analytical and descriptive research. Despite all the struggles and activities carried out to regulate the operations of multinational corporations and the demand of the agents of the main governments responsible for strictly monitoring compliance with the rules (corporate social responsibility) the fact that major multinational corporations are pursuing interests for the implementation oflos control and monitoring of the cross-border activities of their companies should not be ignored. It is concludedthat the government’s support for foreign investment, for example, is sometimes subject to compliance with minimum social, environmental, and human rights standards. It is difficult to judge the success and outcome of the effort made to monitor and regulate the business of multinational corporations, but what seems certain is that rich countries, such as the United States and the United Kingdom, have apparently accepted the task of playing a significant role in promoting and promoting cross-border (corporate social responsibility).